Gadgets Gab at 60 Ghz. - Razavi, B. (IEEE spectrum)
People not only talk on the airwaves, they increasingly expect their gadgets to do the same. The trend began in the late 1990s with Bluetooth, which provided 1 megabit of data per second. Then Wi-Fi and the IEEE 802.11 standard pushed the rate to 100 Mb/s. Now ultrawideband systems are going five times as fast as that.